PENGARUH EARNING PER SHARE, PRICE EARNING RATIO, DEBT TO EQUITY RATIO, DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI 2018-2020 - Mohd. Nawi Purba; Jofana Thalia; Selvica Daniela; Selly Selly (LPPM STIE Muhammadiah Bandung, 2022)
This study aims to test hypotheses and examine the impact of Price Earning Ratio, Earnings Per Share, Debt to Equity Ratio, and Current Ratio on the stock prices of Mining Companies Listed on the IDX in 2018–2021. This study adopted a quantitative methodology and employed a sample technique that included up to 39 samples from 52 firm populations. The findings showed that the stock prices of mining businesses are significantly and positively impacted by EPS, PER, DER, and CR at the same time. While PER has no effect and no major impact on stock prices, EPS and CR have a partly positive and substantial impact, while DER has a partial negative and large impact on stock prices in mining companies listed on the IDX in 2018-2021.